Capital Income Shares and Income Inequality in the European Union - Eva Schlenker; Kai Daniel Schmid (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2013)
In this paper, we measure the effect of changing capital income shares upon inequality of gross household income. Using EU-SILC data covering 17 EU countries from 2005 to 2011 we find that capital income shares are positively associated with the concentration of gross household income. Moreover, we show that the transmission of a shift in capital income shares into the personal distribution of income depends on the concentration of capital income in an economy. Using fixed effect models we find that changing capital income shares play an important role in the development of household income inequality. Hence, in many industrialized countries income inequality has by no means evolved independently from the observed structural shift in factor income towards a higher capital income share over the last decades.
urn:nbn:de:101:1-201403119491
Keywords: D31; D33; E6; E25; 330; Factor Shares; Income Ineuality; EU-SILC; Fixed Effects